Kemandirian Belajar Calon Guru Fisika Melalui Pembelajaran Berbasis LMS: Schoology - Hermansyah, Hermansyah; Yahya, Fahmi; Fitriyanto, Syarif; Musahrain, Musahrain; Nurhairunnisah, Nurhairunnisah (Indonesian Publication Center, 2020)
Face-to-face learning cannot currently be carried out as usual because of the Covid-19 pandemic. The learning process carried out at home is one way to break the chain of the spread of Covid-19. It is very demanding independence of learning from prospective physics teachers. Use of online media based on the Learning Management System (LMS): Schoology is now very necessary to keep the learning process. This study aims to determine the level of learning independence of prospective physics teachers amid the widespread spread of Covid-19 through the application of LMS-based learning: Schoology. This descriptive qualitative research was conducted on prospective physics teachers in the physics education program at Universitas Samawa, Sumbawa Besar. Respondents from this study were 15 people selected by saturated sampling techniques. The instrument in this study used a questionnaire with a Likert scale of 20 statement items as the main data of learning independence of the prospective physics teacher. The results showed that the level of self-directed learning of physics teacher candidates on Universitas Samawa amid the Covid-19 pandemic was in the very high category through the application of LMS: Schoology in learning.